1988
DOI: 10.1080/08964289.1988.9935123
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress in the Health Professions: A Study of Physicians, Nurses, and Pharmacists

Abstract: While considerable research has been devoted to job stress within individual health professions, little information has been available for comparing the sources or levels of stress among different groups of health professionals. To bridge that knowledge gap, the Health Professions Stress Inventory (HPSI) was administered via a mail questionnaire to 291 primary care physicians, 379 registered nurses, and 387 pharmacists randomly selected from across the United States. Mean stress scores on the HPSI were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 6 publications
3
36
1
3
Order By: Relevance
“…This finding is in agreement with previous studies carried out among health care workers in HIV/AIDS units [19]and in other fields of care [20, 21]. It is unclear whether this difference is due to their demographic characteristics (younger) or to work-related issues: nurses have much more direct involvement in the care of seriously ill people and cannot walk away and perform other duties, as doctors can.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in agreement with previous studies carried out among health care workers in HIV/AIDS units [19]and in other fields of care [20, 21]. It is unclear whether this difference is due to their demographic characteristics (younger) or to work-related issues: nurses have much more direct involvement in the care of seriously ill people and cannot walk away and perform other duties, as doctors can.…”
Section: Discussionsupporting
confidence: 82%
“…This finding was revealed in a study using the Health Professions Stress Inventory (HPSI) to compare stress levels among these three groups of health care workers (98). Another study showed significant variations in the levels of occupational stress experienced by health care workers in different units within a hospital (99).…”
Section: Stressmentioning
confidence: 91%
“…Novice professionals may be susceptible to the negative consequences of job stress after leaving their entry-level educational environments (universities) if they do not have assistance in adjusting to the professional world. 25 We also hypothesized that we would find a positive relationship between Carnegie classification level and emotional exhaustion and depersonalization scores (as the Carnegie classification increased, the emotional exhaustion and depersonalization scores would also increase) and a negative relationship between Carnegie classification level and personal accomplishment scores (as the Carnegie classification increased, the personal accomplishment scores would decrease). We did not find a relationship between burnout scores and the different Carnegie classifications.…”
Section: Discussionmentioning
confidence: 99%